Efektifitas Empat Perangkap Serangga dengan Tiga Jenis Atraktan di Perkebunan Pala (Myristica fragrans Houtt) - WINDRA PRIAWANDIPUTRA; AGUS DANA PERMANA (Departemen Biologi, Institut Pertanian Bogor, 2015)
The use of traps for insect surveilance on nutmeg (Myristica fragrans Houtt) plantation is one of the earliest steps in this study since the information of nutmeg pest is barely available. In this study, four traps were used, namely Brown-Black Sticky Trap (BBST), Yellow Sticky Trap (YST), Glass Ambrosia Beetle Trap (GABT), and Plastic Pannel Trap (PPT) placed at 1,5 m high on nutmeg plants around Paya Teuk village (South Aceh). Those traps were accompanied by 35%-ethanol, nutmeg oil, and 35%-ethanol mixed with nutmeg oil as attractans. The observation with 4 types of trap with 3 different attractans and water as control have captured 10 orders, 51 families, 124 morphospecies, and 1027 individuals. Five families with the most numerous individuals were Nitidulidae, Tephritidae, Cicadellidae, Formicidae and Scolitidae. Individuals from Scolitidae and Nitidulidae family were mostly captured by BBST with 35% ethanol, and significantly different with the other traps (two way annova, P<0,05). The number of individuals from Tephritidae were mostly caught by YST using nutmeg oil as an attractan (two way Annova, P<0,05). Each type of trap with a spesific attractan effectively catch a different kind of insect family.